THE FUNCTIONAL CAPATACI OF THE RESPIRATORY AND CARDIOVASCULAR SYSTEMS OF PEOPLE LIVING WITH HIV AT THE STAGE OF AIDS AND THE PROSPECTS FOR ITS IMPROVEMENT BY METHODS AND MEANS OF PHYSICAL THERAPY - Orfin, A. Ya.; Mazepa, M. A. (Rehabilitation and Recreation, 2022)
Objective: to study the functional capacity of the respiratory and cardiovascular systems of PLWH at the stage of AIDS to choose a rational training program. Materials: The study included 24 HIV-infected patients at the stage of AIDS on an outpatient basis. To assess the functional capacity (FC) of the respiratory system, the following were determined: breathing rate (BR), SpO2, Stange and Genchi tests, vital capacity of the lungs (VCL). The hypoxia index (HI), the Hildebrant coefficient (HC) and the circulatory-respiratory coefficient of Skibinskaya (CRCS) were calculated. Studying the FC of the cardiovascular system determined heart rate (HR), blood pressure (BP), pulse pressure (PP), systolic (SBV) and minute (MBV) blood volumes. The coefficients of efficiency of blood circulation (CEBC), endurance (CE), Robinson index (RI) were also calculated. All PLWH were diagnosed with HIV viral load and CD4+ T lymphocyte counts. Results. Two research groups were formed. It was established that the BH was 19.7 ± 1.9 per minute and 21.1 ± 1.8 (p≤0.05) per minute in groups I and II, respectively. SpO2 level, was lower in group I 91.5 ± 1.6 % against 93.2 ± 1.9 % in group II (p≤0.05). In group I, the result of the Genchi test was 32.2 ± 2.7 sec., the Stange – 31.3 ± 5.2 sec. For group II, the data were similar: 29.7 ± 4.3 sec. and 32.2 ±6.6 sec. respectively (p≥0.05). VCL in PLWH group I reached 2639.1 ± 430.3 ml, and in group II – 3144.5 ± 463.3 ml (p≤0.01). IG in group I 0.41 ± 0.05 с. u. and in group II 0.39 ± 0.07 с. u. (p≥0.05). The value of HC is the same in two groups – 3.97 ±0.3 с. u. for group I and 3.98 ± 0.5 с. u. for group II (p≥0.05). The CRCS was lower in Group I 10.91 ± 3.95 с. u. against 13.64 ± 4.81 с. u. in group II (p≥0.05). Studying the FC of the cardiovascular system for group I, it was established: HR 78.4 ± 6.8 bpm, SBP 126.3 ± 14.5 mmHg, DBP 71.3 ± 9.2 mmHg, PP 55.0 ± 14.3 mmHg. In group II, HR was 77.3 ± 7.4 bpm, SBP 123.8 ± 18.2 mmHg, DBP 73.1 ± 7.2 mmHg, PP 50.7 ± 18.3 mmHg. (p≥0.05). MBV and SBV in group I patients were 4302.5 ± 827.8 mL and 55.2 ± 11.4 mL, respectively. And in group II: MBV 4342.0 ± 1250.3 ml and SBV 52.01 ± 12.2 ml (p≥0.05). For group I, the CEBC was 4274.5 ± 1011.1 с. u. and 4217.6 ± 1707.8 с. u. for group II (r≥0.05). CE was higher in group II – 19.1 ± 9.7 с. u., against – 16.3 ± 4.7 с. u. (p≥0.05). The RI reached 98.7 ± 11.01 с. u. and 102.46 ± 17.3 с. u. in groups I and II, respectively. Conclusion. The FC of the respiratory and cardiovascular systems in PLWH is very weak and is characterized by low potential with poor compensatory capacity.